Something borrowed, something mewed - Blake, Bethany (Blake, Bethany. Lucky Paws Petsitting mystery., 2019)
Daphne Templeton<U+2019>s sister Piper is getting married<U+2014>and their mother is getting carried away. She insists on hiring Sylvan Creek<U+2019>s top event planner, Abigail Sinclair, who proposes an Independence Day theme complete with Statue of Liberty-inspired bridesmaid dresses. With all the bickering among the families, Daphne<U+2019>s glad her only duty right now is pet-sitting for Abby<U+2019>s cat, Ms. Peebles. But there are some fireworks coming that aren<U+2019>t part of the ceremony. The Poconos will never be the same . . . At a tension-filled dress fitting, the abrasive wedding planner is found strangled by a garter<U+2014>a weapon both borrowed and blue. Now Daphne<U+2019>s services are required not just for organizing the big day, but for figuring out whether one of the in-laws is an outlaw . . .